PRELIMINARY STUDY REGARDING THE USE OF SOME Yarrowia lipolytica STRAINS FOR SOLID STATE HYDROLYSIS OF CRUDE COCONUT FAT - GEORGIANA PARFENE; VICENTIU BOGDAN HORINCAR; GABRIELA BAHRIM (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Coconut fat could be an important source of bioactive compounds with a large applicability in industry. In this study it was realized the enzymatic hydrolysis of coconut fat with different yeast strains of Yarrowia lipolytica. The aim of this study was to optimize the hydrolysis conditions and determination of Yarrowia lipolytica specificity on coconut fat as substrate. The hydrolysis was performed by yeast strains cultivated on stationary solid state conditions on spirit blue agar medium supplemented with 3% coconut fat, at 25°C and 4°C, and at values of water activity of 0.98, 0.96 and 0.93. The substrate hydrolysis index was recorded every 24 hours, during of 240 hours of stationary cultivation. The most active lipolytic yeast was strain coded S5 which produce a high level of extracellular lipase with high coconut hydrolyze activity at 25°C and two water activities 0.98 and 0.96, in the shortest time (24 – 72 hours). In the presence of 3% NaCl in media, the strains coded S9, S5 and S4 were the most active from all tested strains at 25°C and 4°C. At low temperatures and in presence of 10.1% NaCl all tested yeasts had no lipolytic activity.